INVESTIGATION THE IMPACT OF DIFFERENT ANNEALING TEMPERATURES ON STRUCTURAL AND OPTICAL PROPERTIES OF BI-DOPED GETE (BI: 5 %) THIN FILMS FABRICATED BY PVD TECHNIQUE) - Ahmed, Shayma M.; Jarjes, Azhen H.; Abdulrahman, Ahmed F.; Mohammed, Raghad Y.; Ahmed, Sabah M. (Science Journal of University of Zakho, 2024)
The impact of different annealing temperatures on the Bi-doped GeTe thin films were investigated. The thin films have been prepared by using physical vapor deposition techniques (PVD). The Bismuth (Bi) is doped GeTe with ratio of 5%. Different characterizations techniques have been used to study the different properties of thin films with several annealing temperatures. It has been found that the film thickness decreases as the annealing temperature increases. The XRD patterns show that as-deposited and annealed Bi-doped GeTe films at 150°C,200°C, and 250°C were fully amorphous, while the film annealed at 100 °C was crystalline. FESEM image shows that the structure is amorphous with no grain appearing for the crystallite GeTe compound. Whereas the annealed thin films at 100°C are well-appeared crystallites of GeTe with an average size of (110.64 nm). The thin films are annealed at (150, 200, and 250)°C which reveals that the crystallite or grain is increased. An increase in the annealing temperature has been found to cause a significant shift in the absorption edge toward an extended wavelength and an overall reduction in transmittance. At a wavelength of 1100 nm, the transmittance dropped from 65.25% for as-deposited thin films to 32.57% for annealed thin films at 250 °C. Furthermore, when the annealing temperature rises from 100°C to 250°C, the optical band gap reduces from 0.95 eV to 0.42 eV.